The Sino-American alliance : nationalist China and American cold war strategy in Asi - Garver, John W. (New York : M.E. Sharpe, 1997)
An East Gate book
Keywords: Cold War; Taiwan -- Foreign relations -- United States..; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- Taiwan